The effect of adding dragon fruit peel (Hylocereus polyrhizus) and red ginger extract on characteristics of jelly candy from aloe vera - Fadiyah, Aisy Tsabita Hasibata; Sinaga, Hotnida; Lubis, Linda Masniary (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
This research aimed to determine the effect of adding dragon fruit peel and red ginger extract on the characteristics of jelly candy made from Aloe vera. The study used a randomized  block design (RBD) with two factors: the ratio of Aloe vera and dragon fruit peel (100:0, 90:10, 80:20, and 70:30) and red ginger extract (0%, 5%, and10 %). The parameters analyzed were moisture content, ash content, color value (⁰Hue), reducing sugar content, pH, crude fiber, anthocyanin value, antioxidant IC50, total phenol, as well as the hedonic values of color, aroma, taste, texture, and general acceptance. The results showed that the ratio of Aloe vera and dragon fruit peel significantly affected the ash content, color value (oHue), reducing sugar content, crude fiber, anthocyanin value, antioxidant IC50, total phenol, hedonic of color, and general acceptance. The red ginger extracts significantly affected ash content, color value (oHue), reducing sugar content, antioxidant IC50, total phenol, hedonic aroma, and taste. The interaction between the two factors significantly affected the color value (oHue) and total phenol. The formulation with a ratio of aloe vera:dragon fruit peel (70:30) and  10% red ginger extract yielded the best jelly candy.